Prevalence and prognosis of genetically proven familial hypercholesterolemia in subjects with coronary artery disease and reduced ejection fraction - Lee, Wen-Jane; Chuang, Han-Ni; Hsiao, Tzu-Hung; Lee, Wen-Lieng; Wu, Jen-Pey; Sheu, Wayne H.-H.; Liang, Kae-Woei (Scientific reports, 2023)
Few studies have genetically screened variants related to familial hypercholesterolemia (FH) and investigated their survival impact in patients with coronary artery disease (CAD) and reduced left ventricular ejection fraction (EF). Patients with CAD and reduced EF (< 40%) were enrolled. Their genomic DNAs were sequenced for FH-related genes. All-cause and cardiovascular mortality data served as the major outcome. A total of 256 subjects were analyzed and 12 subjects (4.7%) carried FH-related genetic variants. After a median follow-up period of 44 months, 119 of the study subjects died. Cox survival analysis showed that carrying the FH genetic variant did not have a significant impact on the survival of CAD with reduced EF. However, higher estimated glomerular filtration rate (eGFR), better EF and beta blocker use were protective for a lower all-cause mortality. Further larger studies are needed to evaluate the impact of carrying the FH-related genetic variant on survival of CAD with reduced EF.